2000
DOI: 10.1091/mbc.11.11.3777
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nuclear Export of the 60S Ribosomal Subunit In Vivo

Abstract: In Saccharomyces cerevisiae, the 60S ribosomal subunit assembles in the nucleolus and then is exported to the cytoplasm, where it joins the 40S subunit for translation. Export of the 60S subunit from the nucleus is known to be an energy-dependent and factor-mediated process, but very little is known about the specifics of its transport. To begin to address this problem, an assay was developed to follow the localization of the 60S ribosomal subunit in S. cerevisiae. Ribosomal protein L11b (Rpl11b), one of the ϳ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 95 publications
(109 reference statements)
9
121
1
3
Order By: Relevance
“…Although the Nup84 complex is symmetrically disposed across the nuclear envelope, Nup82 and Gle2 are found on the cytoplasmic face (Suntharalingam and Wente, 2003). Previous work has shown that both the Nup84 and the Nup82 complexes are involved in 60S export (Stage-Zimmermann et al, 2000;Gleizes et al, 2001). …”
Section: Double Mutants Are Blocked For Nmd3 and 60s Exportmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the Nup84 complex is symmetrically disposed across the nuclear envelope, Nup82 and Gle2 are found on the cytoplasmic face (Suntharalingam and Wente, 2003). Previous work has shown that both the Nup84 and the Nup82 complexes are involved in 60S export (Stage-Zimmermann et al, 2000;Gleizes et al, 2001). …”
Section: Double Mutants Are Blocked For Nmd3 and 60s Exportmentioning
confidence: 99%
“…Subsequent cloning and sequencing of two of the synthetic lethal mutants identified them as NMD3 and NUP120. Nmd3 acts as the Crm1-dependent export adapter for the 60S subunit (Ho et al, 2000b;Gadal et al, 2001), whereas Nup120 is a nucleoporin that has previously been shown to be required for efficient 60S export (Stage-Zimmermann et al, 2000). Sequencing the genomic locus of the nmd3 mutant revealed a T-to-A transversion at nt 1514 (nmd3⌬C14), resulting in a premature stop codon that eliminates the C-terminal 14 aa.…”
Section: Genetic Interactions Of Arx1mentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we expressed mutant or wild-type Nmd3 proteins in cells containing GFP fusions to various nucleoporins obtained from the GFP-tagged strain collection (32). Particular emphasis was given to those nucleoporins that had previously been implicated in 60S export ( (17,33,34). For analysis of Nup120, which was absent from the GFP library, we expressed NUP120-GFP from a low copy vector in a nup120 deletion strain.…”
Section: Mutant Nmd3 That Accumulates At the Nuclear Envelope Interacmentioning
confidence: 99%